2019
DOI: 10.3390/su11215926
|View full text |Cite
|
Sign up to set email alerts
|

Can Location-Based Social Media and Online Reservation Services Tell More about Local Accommodation Industries than Open Governmental Data?

Abstract: The paper follows-up ongoing research focusing on the potential of machine-readable data as additional knowledge in the governance of local tourism and destination management organizations (DMOs) in Slovakia. The current focus is on one classic social media (Facebook), one location-based social media (Foursquare), two hybrid travel-related platforms with partial attributes of reservation services (Google Places, TripAdvisor), and two online reservation services (Booking, Airbnb). The global aim is the usage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There have been several studies that illustrate this, by showing how OGD can help, for example, to deliver better transparency. One recent study, for instance, showed that certain aspects of portal design can increase data transparency [59,60], while others have identified usability as a critical transparency factor [61]. However, while this research employs the term 'usability', it refers to the relevance and usefulness of the actual datasets, rather than the usability of the portal through which these datasets are found.…”
Section: Review Of the Literature And Gcc Open Data Portalsmentioning
confidence: 96%
“…There have been several studies that illustrate this, by showing how OGD can help, for example, to deliver better transparency. One recent study, for instance, showed that certain aspects of portal design can increase data transparency [59,60], while others have identified usability as a critical transparency factor [61]. However, while this research employs the term 'usability', it refers to the relevance and usefulness of the actual datasets, rather than the usability of the portal through which these datasets are found.…”
Section: Review Of the Literature And Gcc Open Data Portalsmentioning
confidence: 96%
“…Tripadvisor is offering API access for registered users [114]. Publicly available data has been also scraped anonymously and analyzed by Sidor and colleagues [115]. In another study, TripAdvisor big data has been complemented with Eurostat data to identify spatiotemporal patterns in hospitality in the whole of the EU [116].…”
mentioning
confidence: 99%